Leadership practices that support diverse learners from early childhood through adulthood - Rude, Harvey A.; Banerjee, Rashida (Social Welfare: Interdisciplinary Approach, 2013)
This article addresses the components of leadership and the effective demonstration of leadership behavior that supports strong systems of social welfare from an interdisciplinary perspective. The applications of evidence-based leadership principles are embedded within the context of systems that address the needs of all learners from early childhood through adulthood. Leadership considerations include values-based practice, effective use of data, and team learning for systems improvement.